Chinese Religions: Publications in Western Languages, Volume 3: 1991-1995. Compiled by Laurence G. Thompson, edited by Gary Seaman. - Barrett, T. H. (Buddhist Studies Review, 2002)
Chinese Religions: Publications in Western Languages, Volume 3: 1991-1995. Compiled by Laurence G. Thompson, edited by Gary Seaman. Association for Asian Studies, Ann Arbor 1998. xxi, 147 pp. ISBN 0-924394-39-1.